Astroniumxylon, Schinopsixylon, and Parametopioxylon n. gen. fossil woods from upper Cenozoic of Argentina: taxonomic revision, new taxon and new records. (March 2020) - Franco, M. Jimena; Moya, Eliana; Brea, Mariana; Martínez Martínez, Camila
Abstract: This paper presents new descriptions of Anacardiaceae fossil woods from the Ituzaingó Formation (late Cenozoic) at the Toma Vieja, Curtiembre, and Arroyo El Espinillo localities, Argentina. We describe eight silicified woods assigned to four different species in three genera, one of which, Parametopioxylon crystalliferum n. gen. n. sp., is new. Similarities between these three genera and the six Anacardiaceae species previously recorded from the late Cenozoic in northeastern Argentina are investigated using multivariate analysis techniques (correspondence and cluster analysis). Our study is based on 33 characters scored for 17 fossil specimens (10 Astroniumxylon Brea, Aceñolaza, and Zucol 2001; five Schinopsixylon Lutz, 1979; and two Parametopioxylon n. gen.) and four extant species ( Astronium balansae Engl., Astronium urundeuva Engl., Schinopsis balansae Engl., and Metopium sp.). Our main goal is to determine the wood anatomical features useful for distinguishing among these species. Results of the multivariate analyses support the previous classification where Schinopsixylon is distinguished from Astroniumxylon by having exclusively paratracheal axial parenchyma, ≥30% multiseriate rays, and multiseriate rays that are ≥5 cells wide and commonly 301–400 μm in height. Additionally, we propose that Schinopsixylon heckii Lutz, 1979 is synonymous with S . herbstii Lutz, 1979. A diagnostic key for the fossil species studied is given. Wood anatomy of Anacardiaceae fossil woods from Argentina (late Cenozoic) suggests a warm, dry to semi-humid climate for this region, supporting previous studies.